Mitigation of ice-induced vibrations for wind turbine foundation using damping vibration isolation - Baofeng, Zhang; Rui, Dong; Gang, Wang; Guojun, Wang; Dayong, Zhang (Frontiers in Materials, 2023)
The single pile offshore wind turbine foundation is a typical flexible structure, and the dynamic interac-tion between ice and structure is complex. Ice-induced vibrations can affect the normal operation of the upper motor and the safety of the foundation structure. This paper takes the interaction between ice and offshore platform in the Bohai Sea as the research object and discusses the strategies to mitigate the ice- induced vibrations of offshore wind turbine foundation. Through a simplified mechanical model of a damping vibration isolation system, the relationship between the parameters of the damping isolation layer and the structural damping ratio was analyzed. Based on the numerical simulation results, it was found that the damping isolation layer with a damping ratio of 0.2 can play a better role in controlling structural displacement and acceleration response under the action of steady-state and random ice forces. It provides a reference for the design of ice-resistant and safe operation of the offshore wind turbine.